The acute effect of whole body vibration training on agility, speed and power in male volleyball players - Ho, C.-S.; Chang, C.-Y.; Lin, K.-C.; Chang, C.-H.; Chen, K.-C. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to examine the acute effect of whole body vibration training on agility, speed and power in male volleyball players. Ten college volleyball players volunteered to participate in this study. The vibration training (VT) consisted of 60% with 28 Hz frequencies and 1Omm amplitudes. Counter movement jump (CMJ), blocking agility test (BAT), agility test (AT) and 10 meters sprinting (1 OMS) were performed at pre-test and post-test (60s rest). The peak force (PF). mean force (MF), maximum rate of force development (mRFD) and relative net impulse (RNI) from the CMJs were computed. A repeated measures ANOVA was applied to obtain the variables. The present study indicated that the WBV significantly improves the MF, mRFD and BAT parameters of CMJ and BAT performances excluding the PF. Speed and agility does not seem to be enhanced by VT.